Perbedaan Kadar Hemoglobin pada Remaja Stunting dan tidak Stunting di Posyandu Remaja Wilayah Kerja Puskesmas Lubuk Buaya Padang - Dian Eka Nursyam; Irwadi Irwadi; Rahmi Melfa Widodo (Poltekkes Kemenkes Padang, 2024)
Based on data from the World Health Organization (WHO) in 2020, the prevalence of stunting in children worldwide reached 22% or 149.2 million, making it a global issue. Indonesia ranks second highest in Southeast Asia with a stunting prevalence of 31.8%, following Timor Leste at 48.8%. Adolescent girls suffering from anemia are at risk of becoming anemic pregnant women, as well as experiencing protein-energy deficiency. This increases the likelihood of giving birth to low birth weight (LBW) and stunted babies, along with complications during childbirth. The aim of this study was to examine the differences in hemoglobin levels between stunting and non-stunting adolescents. The study was conducted in 2022 at the adolescent health post of the Lubuk Buaya Padang Health Center, using non-probability sampling through consecutive sampling. This observational study employed a cross-sectional approach and involved 42 female adolescents aged 12-21 years. Quantitative data were processed manually and with computer software, and statistical tests were performed using the t-test at a significance level of α = ≤ 0.05. The results indicated that non-stunting adolescents had an average hemoglobin level of 12.8 g/dl, while stunting adolescents had an average level of 12.0 g/dl. The conclusion of this study is that there is no significant difference in hemoglobin levels between stunting and non-stunting adolescents.